PEMBERDAYAAN PERPUSTAKAAN SEBAGAI SARANA DAKWAH - Kobana Salam; Nurdin Nurdin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
Library is a important source of information for community. A number of research has been carried out to understand how libraries are utilized in supporting community and educational institutions need of information. Instaed dakwah is understood as an activity which heavily dealing with information, little is studies has been carried out to understand how a library can be used to support dakwah activities. This paper shed light how libraries can also be used for dakwah purposes. Through extensive literature review, we found that libraries can also be utilized as instrument to support dakwah activities. A library can provide rich information for every Muslim and Dai in dakwah activities. A lbrary can also be used for self-learning activities relating to islamic teaching, and a library can preserve Islamic valuable historical document and artefact for new Muslim generation. Finally, Muslim can use library as a place to obtain inspiration and ideas through self-study and research. The limitation of this paper is that the data merely relied on litarature review and future research need to be carried out to obta